THE TALE TELLS: REVEALING MADURESE’S SACRED CULTURAL VALUES BEHIND MADURA’S FOLKTALE ENTITLED ASAL MULA SOMBHER TENGGUN - Dewi Maharani (Lakon : Jurnal Kajian Sastra dan Budaya, 2018)
A folktale entitled Asal Mula Sombher Tenggun (The Origin of Tenggun Spring) is a tale which grows and developes in Tenggun Village which is located in Klampis District, Bangkalan Regency - Madura. Analysis of intrinsic elements is used to reveal the values in the folklore through its theme, plot, character and characterization, while the emic approach which is conducted by interviewing local villagers is used to reveal more about cultural values of the story as well as the influence of the folklore on the views of life and habits of the local villagers. The cultural values contained in this folktale are the values of beliefs, patience values, philosophical values, and ethical and moral values that influence the life view of Tenggun Village residents in their daily lives, in worshiping Allah SWT, in respecting and serving leaders and parents and in treating other God's creatures such as animals and plants. This story is the reason behind the holding of annual ritual called Rokat Sombher which is held every year in the month of Muharram as a manifestation of gratitude to God for sustenance in the form of springs which remain a source of water to fulfill the needs of the people of Tenggun Village toward water.